Corrupción y procesos electorales en América Latina - Nieto Flores, Nubia Zulma (Pontificia Universidad Católica del Perú, 2024)
Electoral processes are one of the most important pillars of democracy. Transparent, fair and representative elections are the basis of the Western democracies. However, holding electoral processes does not necessarily guarantee the establishment and exercise of the democracy. Elections based on intimidation, threats, insecurity, fear, violence, harassment, fraud, vote buying, abuse, manipulation and exploitation of vulnerable conditions are threats to democracy and an expression of the exercise of corruption. Latin America in recent years has been characterized by adopting democratic governments. In recent decades, almost all countries in the region have managed to overthrow authoritarian, military and dictatorial governments. However, the democratic exercise of citizens in local, regional and national elections is often questioned due to the lack of integrity and transparency of the processes. In this context, this article aims to analyze the role of corruption in electoral processes in Latin America in the last decades. The hypothesis that guides this work is based on the assumption that holding elections does not necessarily guarantee the exercise of democracy, since corruption permeates electoral processes. The text uses qualitative and based on data provided by national and international institutions, analysis and case studies, global reports and journalistic notes, as well as historical sources. The text is divided into three sections. The first exposes some basic concepts of electoral democracy and the threat of corruption. The second presents the effects of corruption materialized in electoral fraud, vote buying, disappearance of ballot boxes, manipulation in digital systems, application of Artificial Intelligence, sponsorship of criminal groups towards a certain candidate, use of criminal forces to intimidate, murder, destabilize electoral processes. The third offers some examples of highly questioned electoral processes in Latin America, and finally some conclusions are made, leaving the door open to future studies that can contribute to reduce the risks of corruption in electoral processes in the Latin American region and help mature the young democracy.

Los procesos electorales son uno de los pilares más importantes de la democracia. Elecciones transparentes, justas y representativas son el sustento de las democracias occidentales. Sin embargo, sostener procesos electorales no necesariamente garantiza la instauración o ejercicio de la democracia. Elecciones fundadas en intimidación, amenazas, inseguridad, miedo, violencia, acoso, fraude, compra de votos, abuso, manipulación y explotación de condiciones de vulnerabilidad son amenazas a la democracia y expresión del ejercicio de la corrupción. América Latina en años recientes se ha caracterizado por adoptar gobiernos democráticos. En las últimas décadas casi todos los países de la región han logrado derrocar a gobiernos autoritarios, militares y dictatoriales. No obstante, el ejercicio democrático de los ciudadanos en elecciones locales, regionales y nacionales a menudo es cuestionado por la falta de integridad y transparencia. En este contexto, el presente artículo tiene como objetivo analizar el rol de la corrupción en los procesos electorales en América Latina en la última década. La hipótesis que guía el presente trabajo parte del supuesto que sostener elecciones no necesariamente garantiza el ejercicio de la democracia, en tanto la corrupción impregna los procesos electorales. El texto consulta de datos arrojados por instituciones nacionales e internacionales, análisis y estudios de caso, reportes globales y notas periodísticas, así como fuentes históricas. El texto se divide en tres apartados. El primero expone algunos conceptos básicos de la democracia electoral y la amenaza de la corrupción. El segundo presenta los efectos de la corrupción materializada en el fraude electoral, compra de votos, desaparición de urnas, manipulación en sistemas digitales, aplicación de Inteligencia Artificial, patrocinio de grupos criminales hacia determinado candidato, uso de las fuerzas criminales para intimidar, asesinar y desestabilizar los procesos electorales. El tercero ofrece algunos ejemplos de procesos electorales altamente cuestionados en América Latina, y finalmente se hacen algunos comentarios conclusivos, dejando la puerta abierta a futuros estudios que puedan contribuir a reducir los riesgos de corrupción en procesos electorales de la región Latinoamericana y ayudar a madurar la joven democracia.
Corruption and Electoral Processes in Latin America
Keywords: Electoral processes; Latin America; Corruption; Democracy; Democratic transition; Elecciones; América Latina; Corrupción; Democracia; Transición democrática; https://purl.org/pe-repo/ocde/ford#5.06.00